Implementation of C-reactive protein point of care testing to improve antibiotic targeting in respiratory illness in Vietnamese primary care (ICAT): a study protocol for a cluster randomised controlled trial - Thi Thuy Do, N; Greer, RC; Lubell, Y; Dittrich, S; Vandendorpe, M; Nguyen, VA; Ngoc Thach, P; Thi Dieu Ngan, T; Van Kinh, N; Hung Thai, C; Dung, LTK; Nguyen Thi Cam, T; et al. (BMJ Publishing Group, 2020)
Introduction C-reactive protein (CRP), a biomarker of infection, has been used widely in high-income settings to guide antibiotic treatment in patients presenting with respiratory illnesses in primary care. Recent trials in low- and middle-income countries showed that CRP testing could safely reduce antibiotic use in patients with non-severe acute respiratory infections (ARIs) and fever in primary care. The studies, however, were conducted in a research-oriented context, with research staff closely monitoring healthcare behaviour thus potentially influencing healthcare workers’ prescribing practices. For policy-makers to consider wide-scale roll-out, a pragmatic implementation study of the impact of CRP point of care (POC) testing in routine care is needed. Methods and analysis A pragmatic, cluster-randomised controlled trial, with two study arms, consisting of 24 commune health centres (CHC) in the intervention arm (provision of CRP tests with additional healthcare worker guidance) and 24 facilities acting as controls (routine care). Comparison between the treatment arms will be through logistic regression, with the treatment assignment as a fixed effect, and the CHC as a random effect. With 48 clusters, an average of 10 consultations per facility per week will result in approximately 520 over 1 year, and 24 960 in total (12 480 per arm). We will be able to detect a reduction of 12% to 23% or more in immediate antibiotic prescription as a result of the CRP POC intervention. The primary endpoint is the proportion of patient consultations for ARI resulting in immediate antibiotic prescription. Secondary endpoints include the proportion of all patients receiving an antibiotic prescription regardless of ARI diagnosis, frequency of re-consultation, subsequent antibiotic use when antibiotics are not prescribed, referral and hospitalisation. Ethics and dissemination The study protocol was approved by the Oxford University Tropical Research Ethics Committee (OxTREC, Reference: 53–18), and the ethical committee of the National Hospital for Tropical Diseases in Vietnam (Reference:07/HDDD-NDTW/2019). Results from this study will be disseminated via meetings with stakeholders, conferences and publications in peer-reviewed journals. Authorship and reporting of this work will follow international guidelines. Trial registration details NCT03855215; Pre-results.